CONTRIBUIÇÕES AO CONHECIMENTO DA HIDROLOGIA SUBTERRÂNEA DO MUNICÍPIO DE SOROCABA (SP) - Yoshinaga, S.; Oda, G. H.; Hirata, R. C. A.; Castro, S. A. P. de; Hassuda, S.; Iritani, M. A.; Otsubo, O. M.; Guzzi, R. J. de; Esteves, T. C. (Águas Subterrâneas, 1990)
Inexistente.